Multi-response optimization of wire bonding process for evaluating alternative wire material. (December 2020) - Lin, Chun-Ting; Lin, Chen-ju
Abstract: Finding an alternative material to gold wire is important to cost reduction for the wire bonding process. The wire materials for laser diodes are required to pass ball shear test, wire pull test and several reliability tests, so that it can be used in production. This research employs the Multi-response Quality Test procedure that investigates the feasibility and optimal conditions of using silver alloy wire in the wire bonding process. The weighted Principal Components Analysis-based Taguchi method is used to determine the optimal parameter combination of the wire bonding process, which can minimize quality loss in multiple tests. The result shows that under the optimal parameter combination of the wire bonding process, silver alloy wire can outperform gold wire by having higher ball bond strength, higher wire strength, and smaller operation current changes after the reliability tests. Substituting gold wire with silver alloy wire can significantly reduce cost by 30% while improving wire bond quality. Highlights: Replacing gold wire with silver alloy wire can improve wire bonding quality. A Multi-response Quality Test procedure is introduced to evaluate the alternative. The evaluation procedure analyzes several responses of mechanical and reliability tests. The optimal parameter design of wire bonding process is obtained. The annual material cost savings are approximately 660, 100 USD.